Size distribution and ionic composition of marine summer aerosol at the continental Antarctic site Kohnen - R. Weller; M. Legrand; S. Preunkert (Atmospheric Chemistry and Physics, 2018)
We measured aerosol size distributions and conducted bulk and size-segregated aerosol sampling during two summer campaigns in January 2015 and January 2016 at the continental Antarctic station Kohnen (Dronning Maud Land). Physical and chemical aerosol properties differ conspicuously during the episodic impact of a distinctive low-pressure system in 2015 (LPS15) compared to the prevailing clear sky conditions. The approximately 3-day LPS15 located in the eastern Weddell Sea was associated with the following: marine boundary layer air mass intrusion; enhanced condensation particle concentrations (1400 ± 700 cm−3 compared to 250 ± 120 cm−3 under clear sky conditions; mean ± SD); the occurrence of a new particle formation event exhibiting a continuous growth of particle diameters (Dp) from 12 to 43 nm over 44 h (growth rate 0.6 nm h−1); peaking methane sulfonate (MS−), non-sea-salt sulfate (nss–SO42−), and Na+ concentrations (190 ng m−3 MS−, 137 ng m−3 nss–SO42−, and 53 ng m−3 Na+ compared to 24 ± 15, 107 ± 20, and 4.1 ± 2.2 ng m−3, respectively, during clear sky conditions); and finally an increased MS− ∕ nss–SO42− mass ratio βMS of 0.4 up to 2.3 (0.21 ± 0.1 under clear sky conditions) comparable to typical values found at coastal Antarctic sites. Throughout the observation period a larger part of MS− could be found in super-micron aerosol compared to nss–SO42−, i.e., (10 ± 2) % by mass compared to (3.2 ± 2) %, respectively. On the whole, under clear sky conditions aged aerosol characterized by usually mono-modal size distributions around Dp =  60 nm was observed. Although our observations indicate that the sporadic impacts of coastal cyclones were associated with enhanced marine aerosol entry, aerosol deposition on-site during austral summer should be largely dominated by typical steady clear sky conditions.